2014
DOI: 10.1002/eji.201344179
|View full text |Cite
|
Sign up to set email alerts
|

Integrin receptors on tumor cells facilitate NK cell‐mediated antibody‐dependent cytotoxicity

Abstract: NK cells that mediate ADCC play an important role in tumor-specific immunity. We have examined factors limiting specific lysis of tumor cells by CD16.NK-92 cells induced by CNTO 95LF antibodies recognizing αV integrins that are overexpressed on many tumor cells. Although all tested tumor cells were killed by CD16.NK-92 effectors in the presence of the antibodies, the killing of target cells with a low level of ICAM-1 expression revealed a dramatic decrease in their specific lysis at high antibody concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…SKBR3 cells have a low level of ICAM-1 that serves as a ligand for ␤ 2 integrins on CD16.NK-92 cells (7). We have shown that treatment of SKBR3 with IFN-␥ for 48 h results in significant up-regulation of cell-surface ICAM-1 molecules but not Her2/neu receptor (7).…”
Section: Ligation Of ␤ 2 Integrins Accelerates the Kinetics Of Targetmentioning
confidence: 77%
See 3 more Smart Citations
“…SKBR3 cells have a low level of ICAM-1 that serves as a ligand for ␤ 2 integrins on CD16.NK-92 cells (7). We have shown that treatment of SKBR3 with IFN-␥ for 48 h results in significant up-regulation of cell-surface ICAM-1 molecules but not Her2/neu receptor (7).…”
Section: Ligation Of ␤ 2 Integrins Accelerates the Kinetics Of Targetmentioning
confidence: 77%
“…Herceptin, humanized antibody against human HER2/neu used in this study have been previously described (7,9). Hybridomas producing mouse blocking antibody TS1/18 specific for human CD18 (␤ 2 integrin chain), mouse non-blocking TS2/4 antibody against human CD11a (␣ L integrin chain), mouse blocking antibody R6.5 specific for human ICAM-1, and mouse 3G8 antibody specific for human CD16 were purchased from ATCC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, JAM-A-JAM-A binding may also have been involved in our celladhesion assay. ICAM-1 is both a cell surface glycoprotein that belongs to the Ig superfamily and a costimulatory molecule that provides signals to cytotoxic T lymphocytes and NK cells (46,47). Increasing evidence suggests that ICAM-1 plays a functional role on the tumor cell surface.…”
Section: Discussionmentioning
confidence: 99%